(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Plasma treatment is an emerging surface modification technique that alters dye uptake of wool without using chemicals or water for pre-treatment. Padding is an established continuous dyeing technique known for its efficient use of water, time and energy. This study combined these two techniques for colouration of wool fabric using two natural dyes derived from the Acacia plant family. The investigation focused on the effects of plasma treatment and obtaining unique patterning effects. Helium (100%) and a mixture of helium and nitrogen (95%/5%) were used as the plasma gases under atmospheric conditions. Plasma treated wool fabric was padded with the above natural dyes. Copper sulphate and ferrous sulphate were applied on the dyed fabric as mordant yielding neutral shades of beige and grey respectively. Up to a 30% enhancement of dye adsorption on plasma treated wool substrate was observed as compared to untreated sample for both gases used. This higher adsorption indicates the hydrophilic character of the natural dyes used. Key performance parameters such as fastness to washing, rubbing and light were tested and found to be satisfactory. A single process tone-on-tone pattern was achieved by controlling the plasma exposure of treated area. This study concluded that a merger of natural dyes with modern plasma treatment and padding techniques for wool colouration was feasible.